2016
DOI: 10.1080/15389588.2015.1067803
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of multibody and finite element human body models in pedestrian accidents with the focus on head kinematics

Abstract: There are differences in kinematics between the THUMS and TNO pedestrian models. However, these model differences are of the same magnitude as those induced by other uncertainties in the accident reconstructions, such as initial leg posture and pedestrian velocity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…By using THUMS (version 1.4), Alvarez [13] investigated the influence of neck muscle activation in a simulation of a pedestrian accident, and addressed the effect of muscle activation on strain in the brain, when initiated at the time of head contact. Fahlstedt [14] compared and evaluated the difference in head kinematics between the Netherlands Organization for Applied Scientific Research (TNO) and THUMS (version 1.4) models in pedestrian accident situations. It was found that, although there were differences in kinematics between the THUMS and TNO pedestrian models, the two models showed similar trends for the head trajectory when various parameters were altered.…”
Section: Introductionmentioning
confidence: 99%
“…By using THUMS (version 1.4), Alvarez [13] investigated the influence of neck muscle activation in a simulation of a pedestrian accident, and addressed the effect of muscle activation on strain in the brain, when initiated at the time of head contact. Fahlstedt [14] compared and evaluated the difference in head kinematics between the Netherlands Organization for Applied Scientific Research (TNO) and THUMS (version 1.4) models in pedestrian accident situations. It was found that, although there were differences in kinematics between the THUMS and TNO pedestrian models, the two models showed similar trends for the head trajectory when various parameters were altered.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the time efficiency of the currently used two pedestrian models (the full-scale MB TNO pedestrian model and the CPCBM) were compared and evaluated by simulating the same typical car-to-pedestrian impact scenario ( Figure 9) at 40 km/h lasting 240 ms using a PC with 8-core i7 CPU (Intel Core). Since the time efficiency disadvantage of the full-scale FE model was well-known [25], the THUMS pedestrian model was also included in the comparison (see Table 4). In order to ensure the comparability of the results of the models, the mass scaling percentage of all FE models were limited to 2%, and hourglass control algorithms were used to keep the ratio of hourglass energy to the total energy less than 10%, as per the recommendations of Yang and King [55].…”
Section: Calculation Efficiency Of the Human Body Modelsmentioning
confidence: 99%
“…Compared to the MB model, the advantage of the FE model, being able to represent detailed human anatomical structure, makes it possible to study human tissue level injuries. However, the FE model requires high computational resources for the model adjustment and computations, which means that it is not realistic to conduct complicated traffic accident reconstruction using solely the FE model [25].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations